IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI RELIGIUS PESERTA DIDIK - Syukur, Abdul; Ismail, Ismail; Palili, Sampara (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyse the implementation of Islamic Religious Education (PAI) in instilling religious values in students at Yukartuni Junior High School (SMPLB) in Makassar City. This research is a type of qualitative research with a case study approach that prioritises an in-depth understanding of the practice of religious education in students with special needs. Data were obtained through direct observation, interviews with teachers and principals, and learning documentation. The research findings show three main points related to the implementation of religious education at SMPLB Yukartuni. Firstly, the learning strategies applied use an experiential approach and adaptive technology that is effective in attracting students' interest. The personal approach taken by teachers in teaching also proved successful in building closer relationships with students, thus facilitating the understanding of Islamic values. Secondly, the main challenge in implementing PAI is the limited infrastructure and facilities as well as the lack of specialised competence possessed by teachers in handling learners with special needs. This affects the quality of learning and its impact on students' religious understanding. Thirdly, although the impact of Islamic religious education is seen in the increased moral awareness and religiosity of learners, there are still variations in religious understanding among learners with diverse needs, indicating the need for further adjustments in learning methods. This study recommends increased training for teachers, provision of more adequate facilities, and strengthening collaboration between schools, families and communities to optimise the implementation of Islamic religious education in special schools. ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi Pendidikan Agama Islam (PAI) dalam menanamkan nilai-nilai religius pada peserta didik di Sekolah Menengah Pertama Luar Biasa (SMPLB) Yukartuni Kota Makassar. Penelitian ini adalah jenis penelitian kualitatif dengan pendekaan studi kasus yang mengutamakan pemahaman mendalam tentang praktik pendidikan agama pada siswa dengan kebutuhan khusus. Data diperoleh melalui observasi langsung, wawancara dengan guru dan kepala sekolah, serta dokumentasi pembelajaran. Temuan penelitian menunjukkan tiga poin utama terkait dengan implementasi PAI di SMPLB Yukartuni. Pertama, strategi pembelajaran yang diterapkan menggunakan pendekatan berbasis pengalaman dan teknologi adaptif yang efektif untuk menarik minat peserta didik. Pendekatan personal yang dilakukan oleh guru dalam mengajar juga terbukti berhasil membangun hubungan yang lebih erat dengan siswa, sehingga mempermudah pemahaman nilai-nilai agama Islam. Kedua, tantangan utama dalam implementasi PAI adalah keterbatasan sarana prasarana serta kurangnya kompetensi khusus yang dimiliki oleh guru dalam menangani peserta didik dengan kebutuhan khusus. Hal ini mempengaruhi kualitas pembelajaran dan dampaknya terhadap pemahaman agama siswa. Ketiga, meskipun dampak pendidikan agama Islam terlihat pada peningkatan kesadaran moral dan religiusitas peserta didik, masih terdapat variasi dalam pemahaman agama di antara siswa dengan kebutuhan yang beragam, yang menunjukkan perlunya penyesuaian lebih lanjut dalam metode pembelajaran. Penelitian ini merekomendasikan peningkatan pelatihan bagi guru, penyediaan sarana yang lebih memadai, serta penguatan kolaborasi antara sekolah, keluarga, dan masyarakat untuk optimalisasi penerapan pendidikan agama Islam di sekolah luar biasa.